Information age (New York : EVN, 2002)
This program explained what is information age and discovers about electricity, radio, television, setellites, cell phones, computers and the internet.
Executive producer, George H. Russell ; graphic assistants, Keshia Johnson, Lindsay Huck
Narrator: Linda Mares
Keywords: Information society; Information technology -- Social aspects